Receptor Measurements via Tc-GSA Kinetic Modeling Are Proportional to Functional Hepatocellular Mass - Miki, Kenji; Kubota, Keiichi; Inoue, Yusuke; Vera, David R; Makuuchi, Masatoshi (The Journal of nuclear medicine (1978), 2001)
Kinetic modeling of 99mTc-diethylenetriaminepentaacetic acid galactosyl human serum albumin (Tc-GSA) measures the total amount of asialoglycoprotein receptor within a subject's liver. This study tested the hypothesis that the amount of asialoglycoprotein receptor measured by Tc-GSA modeling provides a valid index of functional liver mass. Twenty-two patients with cirrhosis, 18 patients with chronic hepatitis, and 9 patients with normal liver parenchyma were studied with Tc-GSA using a 30-min dynamic imaging protocol. The total amount of hepatic receptor was measured by kinetic modeling of the Tc-GSA time-activity data. The total number of viable hepatocytes was calculated using standard morphometric measurements of liver biopsy samples and liver volume measurements through CT. The total receptor amount strongly correlated with the total hepatocyte number (r = 0.803; P < 0.0001). Tc-GSA measurement of the total receptor amount is proportional to the number of viable hepatocytes and therefore provides a valid assessment of functional liver mass.